Literacy and deaf education toward a global understanding - Wang, Qiuying; Andrews, Jean F. 1951- (Gallaudet University Press, 2020)
"This contributed volume provides a global view of recent theoretical and applied research that focuses on literacy education for deaf learners"--
Keywords: Inklusive Pädagogik; Gehörloser Mensch; Schreibenlernen; Deaf / Education; Reading; Literacy; Aufsatzsammlung